Unravelling the taxonomy and distribution of two problematic small mammal genera in the Karoo biome. Issue 3 (4th October 2019) - Main, Devon; Tensen, Laura; Gihring, Katharina; Bronner, Gary; Aboul-Hassan, Nadine; Blanckenberg, Michelle; van Vuuren, Bettine Jansen
Abstract : South Africa harbours remarkable biological diversity with three of the 34 recognised global biodiversity hotspots placed within its borders. One of these is the Succulent Karoo, which together with the Nama-Karoo, forms the Greater Karoo region. Notwithstanding a paucity of studies from this region, it would appear that, although mammal diversity is low, endemism is high. Here, as part of the Karoo BioGaps project, we use a molecular approach to assess small mammal diversity and endemism in the Karoo. We focus on rock rats ( Micaelamys ) and elephant shrews ( Elephantulus and Macroscelides ). Using a DNA-informed identification approach, we reveal two, well supported, monophyletic clades of Micaelamys ; one that corresponds to M. granti . Our study is the first to publish sequence data for this species. Furthermore, when unverified records are excluded, the range of M. granti is far smaller (∼99 000 km 2 ) than that given by the IUCN red list assessments (236 027 km 2 ), which lends support to the species being a Karoo endemic. Our macrosceledid samples grouped into four well supported clades of the genera Elephantulus and Macroscelides . Very high intraspecific diversity was present within E. pilicaudus compared with other species in our study and this newly described species may harbour cryptic diversity. Our geographic analyses confirm that the range of this species, previously considered to be a Nama-Karoo endemic, extends beyond this region. This study adds more information to the nominal data currently available for the species, Elephantulus pilicaudus .